2015
DOI: 10.3727/096368915x686184
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating of Pancreatic Islets with Neural Crest Stem Cells Improves Engraftment and Function after Intraportal Transplantation

Abstract: The present study aimed to develop techniques for surface coating of islets with neural crest stem cells (NCSCs) in order to enable cotransplantation to the clinically used liver site and then investigate engraftment and function intraportally of such bioengineered islets. Mouse islets were coated during incubation with enhanced green fluorescent protein (EGFP)-expressing mouse NCSCs and transplanted into the portal vein to cure diabetic mice. An intravenous glucose tolerance test was performed at 1 month post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The improved SOD1 G93A MN survival coincided with the presence of direct contacts between bNCSCs and SOD1 G93A MNs, suggesting that the positive effect of bNCSCs might be mediated through intercellular connections, as was shown previously in bNCSC-beta-cell cultures [29]. We have also shown that bNCSCs produce a broad range of trophic factors, as well as Wnt-1 and matrix metalloproteinases [35]. This trophic capacity, in co-operation with direct cell-cell interaction, may explain the survival promoting effects of bNCSCs on SOD1 G93A MNs under stressful conditions in vitro .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The improved SOD1 G93A MN survival coincided with the presence of direct contacts between bNCSCs and SOD1 G93A MNs, suggesting that the positive effect of bNCSCs might be mediated through intercellular connections, as was shown previously in bNCSC-beta-cell cultures [29]. We have also shown that bNCSCs produce a broad range of trophic factors, as well as Wnt-1 and matrix metalloproteinases [35]. This trophic capacity, in co-operation with direct cell-cell interaction, may explain the survival promoting effects of bNCSCs on SOD1 G93A MNs under stressful conditions in vitro .…”
Section: Discussionsupporting
confidence: 63%
“…However, the presence of GFP + MNs at a distance from bNCSCs and in the vicinity of the central canal one week after implantation indicates that some implanted SOD1 G93A MN precursors rapidly become independent of close contact with bNCSCs. Survival of migrated SOD1 G93A MNs may be supported by bNCSC-derived diffusible molecules, such as vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), glial-derived neurotrophic factor (GDNF), and ciliary neurotrophic factor (CNTF) [35], all of which have trophic effects on MNs [37]. bNCSC-derived matrix metalloproteinase-2 and -9 (MMP-2 and -9) [36], which have been implicated in cell migration [38, 39], may contribute to the migratory capacity of implanted SOD1 G93A MNs to the spinal cord parenchyma and in some cases towards the central canal (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neural crest stem cells ( NCSCs ) are other supporting cells that have been used to improve islet transplantation, increasing both islet reinnervation and revascularization (Lau, Vasylovska, Kozlova, & Carlsson, ).…”
Section: Tissue Engineering In Islet Transplantationmentioning
confidence: 99%
“…Dendritic cells (DCs) are potent antigen-presenting cells that play an important role in innate and adaptive immunity by inducing and modulating T cell activation. DC-based immunotherapeutic approaches have been developed to prevent and reverse T1D (Mukherjee & Dilorenzo, 2010 Finally, neural crest stem cells (NCSCs) are other supporting cells that have been used to improve islet transplantation, increasing both islet reinnervation and revascularization (Lau, Vasylovska, Kozlova, & Carlsson, 2015).…”
Section: Accessory Cellsmentioning
confidence: 99%
“…In addition to their robust survival and broad differentiation potential, they display a remarkable ability to promote survival and support the function of different types of co-cultured cells. Thus, bNCSCs stimulate proliferation of co-cultured (Grouwels et al, 2012;Ngamjariyawat, Turpaev, Vasylovska, Kozlova, & Welsh, 2013;Ngamjariyawat, Turpaev, Welsh, & Kozlova, 2012;Wang et al, 2016) and co-implanted insulinproducing pancreatic beta-cells (Lau, Vasylovska, Kozlova, & Carlsson, 2015;Olerud et al, 2009). Co-transplantation of bNCSCs and human pancreatic islets increased islet vascularization and innervation, most likely mediated by diffusible factors released from the bNCSCs (Grapensparr et al, 2015;Lau et al, 2015).…”
mentioning
confidence: 99%